Characterization of Palm Oil Mill Fly Ash Based Adsorbent as Bleaching Agent of Crude Palm Oil - Pelita, Elda; Desniorita, Desniorita; Nirmala, Dyah; Youfa, Rita; Jayanti, Regna Tri; Sahaq, Anang Baharuddin; Permadani, Resi Levi (Universitas Jenderal Soedirman, 2026)
ABSTRACT. The palm oil industry generates significant waste, including fly ash (FA) from palm oil mill boilers, which poses environmental challenges. This study investigated the potential of FA as an alternative adsorbent for the bleaching of crude palm oil (CPO) and compared its performance with commercial bleaching earth (BE). FA was activated thermally at 400°C and chemically using 1.5 M oxalic acid solution to enhance its adsorption capacity. The results showed that chemically activated FA (FA 1.5 M) and thermally activated FA (FA 400°C) reduced the CPO color from 20 Red (R) to 16-17 R, meeting the industrial standard for degummed bleached palm oil (≤ 17 R). The bleaching efficiency of FA 1.5 M was comparable to that of BE under identical conditions (120 °C and 1.5% w/w adsorbent), demonstrating its practical applicability as an alternative bleaching agent. Characterization results showed that FA 1.5 M had a higher silica (SiO₂) content (77.13%) than FA 400°C (72.46%) and BE (52.01%), along with increased surface area and pore size. FTIR analysis confirmed the adsorption of organic components from CPO onto the activated FA surface, while SEM analysis revealed that chemical activation produced a rougher surface morphology with larger pore diameters. Heavy metal concentrations in both activated FA adsorbents were within safe limits for food applications. Furthermore, BET analysis confirmed that FA 1.5 M exhibited a mesoporous structure with improved adsorption isotherms compared to untreated FA. The study showed that FA particularly FA 1.5 M, shows strong potential as an effective, low-cost, and environmentally sustainable alternative adsorbent in the CPO bleaching process. Keywords: Adsorbent, Bleaching earth, Crude palm oil, Fly ash